If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x=4+1/3
We move all terms to the left:
x-(4+1/3)=0
We add all the numbers together, and all the variables
x-(1/3+4)=0
We get rid of parentheses
x-4-1/3=0
We multiply all the terms by the denominator
x*3-1-4*3=0
We add all the numbers together, and all the variables
x*3-13=0
Wy multiply elements
3x-13=0
We move all terms containing x to the left, all other terms to the right
3x=13
x=13/3
x=4+1/3
| 0.5(4x+10)=6 | | 2x+8.2=90.4 | | 5x+2=8x-11 | | X+55+139=41+x+96 | | 20-6n=-2n+12 | | -5x+6(2x+2)=-37 | | -m-7=-37 | | 20-8n=-12 | | 41/2a+31/4a=217 | | |m|=-6 | | 0.5x-20=1-1.6x | | 6y-0.75=-6.75 | | 38x+7=13 | | 6x+7+85=18x-4 | | 3x+20=5x+14 | | -2x+13=-25 | | 8(v+4)=3v+22 | | (X*x)+10=7x | | 6x+1=109 | | 3(p-2)+5=14 | | 3(5x-2=69 | | 5x-33=3(x-5) | | 5.8f-18.3=6.74 | | 13-6.7x=1-0.7x | | 9x+1=22 | | 6x+3=2(3x-7) | | 5(v-2)=8v-19 | | -x+19=26 | | (X+3)*x=108 | | 3.5v=11 | | 52(x-2)+2x-4=9 | | c/8=1.85 |